Akuntansi Air, Manajemen Impresi, dan Biaya Ekuitas: Studi Bibliometrik - Santoso, Arif; Setiawan, Doddy (Jurnal Akuntansi dan Bisnis, 2023)
This study aims to visualize research trends regarding water accounting, impression management, and the cost of capital with various variables in the network. The research method uses a bibliometric study with VOSviewer analysis. Publication of article data was obtained from Scopus for the period 2013-2023. This research found that publications on water accounting, impression management, and cost of capital grew rapidly from 2019 to mid-2023. The United States dominated in the most publications category and China dominated in the most productive author and funding sponsor categories. The results also show that this research topic has a publication area that covers the scope of business, accounting, finance, economics, management, business psychology, and the environment. Furthermore, this study contributes to providing an overview of the next research agenda.